Effect of Infusion Buas-Buas Leaf (Premna serratifolia Linn.) on Decreasing Blood Glucose Level of Alloxan-Induced White Mice - Marliana, Anis; Helmidanora, Rusdiati (Universitas Muhammadiyah Kalimantan Timur, 2023)
The prevalence of diabetes is incresing year by year, indicates that there is a need for diabetes treatment. One alternavite treatment for diabetes melitus uses traditional medicine which has relatively small effect when compared to synthetic diabetes melitus drugs use the long term. One plant buas-buas which is utilized a natural therapy to blood glucose levels leaves buas-buas (Premna serratifolia Linn). that are believe have antiabetic effect. The study was to determine infusion of buas-buas leaves can decreas blood glucose levels in alloxan-induced mice. The research is experimental using purposive sampling. Method collection sample, make simplisia of buas-buas leaves, extracing buas-buas leaves and antidiabetic test on 25 male white mice. The test was conducted by divid into 5 treatments groups, namely positive control (metformin), negative control (aquadest), and control treatment preparations with concentrations of 10, 20, and 40 %. Mice were induced alloxan with dose of 200 mg/kg BB intraperitoneally and give after blood glucose levels 200 mg/dL, then measurd blood glucose levels of mice on day 7 and day 14. The data result were analyzed using Kruskall Wallis Test. The results of study indicate that infusion of wild buas leaves can decreas blood glucose levels. A dose of wild buas leaf infusion with a concentration of 20 % is effective in decreasing blood glucose levels.